Application of the Classification Decision Tree Method to Determine Student Satisfaction Factors for Student Services - Yuda Perwira; Amran Sitohang; Mutiara Pandjaitan; Kuza Simamora (Jurnal Info Sains : Informatika dan Sains, 2023)
This study aims to apply the Classification Decision Tree method in knowing the factors that influence student satisfaction with student services in tertiary institutions. The Classification Decision Tree method is used to build a decision tree model that can identify the factors that most influence student satisfaction.The data used in this study is survey data on student satisfaction with student services in tertiary institutions, which consists of several variables such as service quality, facilities, information availability, and others. The data will be processed using the Classification Decision Tree algorithm to build a decision tree model that can predict student satisfaction based on the factors that influence it.The results of this study obtained an important root or root of student satisfaction with student services. The first is student welfare services and the second is organizational development services and the results of the test data show an accuracy of 87%.